Pengembangan Penilaian Merdeka Belajar Satuan Pendidikan SMA/MA - Elly Damayanti Pulungan; Sulastri Sulastri; Neysa Vania Nasution; Nurmawati Nurmawati; Rusydi Ananda (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The advancement of independent learning assessment in secondary education (SMA/MA) is intended to establish a more adaptable assessment system that aligns with students' needs and offers a thorough view of their capabilities. This approach can greatly encourage students to engage in learning and enhance the quality of education. Considering the importance of exploring and understanding the concept of independent learning assessment in secondary schools in Indonesia, this study aims to describe the process of developing independent learning assessment in SMA/MA institutions, utilizing a library research methodology. The findings reveal that, in practice, the implementation of independent learning assessment in SMA/MA does not significantly differ from other educational levels or previous curricula. Nonetheless, the policy on developing independent learning assessment grants students greater autonomy in how their learning occurs, provides increased motivation and innovation, and allows students to select their learning pathways based on their individual talents, interests, and skills.